SuPAR, an emerging biomarker in kidney and inflammatory diseases. Issue 1115 (3rd September 2018) - Hamie, Lamiaa; Daoud, Georges; Nemer, Georges; Nammour, Tarek; El Chediak, Alissar; Uthman, Imad W; Kibbi, Abdul Ghani; Eid, Assaad; Kurban, Mazen
Abstract: Soluble urokinase plasminogen activator receptor (suPAR) is a circulating form of a physiological and pathophysiological important cell surface receptor, implicated in inflammation. Recent studies showed that suPAR is a promising biomarker, useful for diagnosis, assessment and prognosis of several diseases. This review summarises the majority of preliminary studies and analyses the significance and the clinical application of suPAR in various clinical conditions. SuPAR seems to have a significant value in the diagnosis as well as prognosis of many diseases; nonetheless, it merits large-scale studies to set cut-off values that help physicians in following up their patients and accordingly tailor their treatment plans.